Chloroquine potentiates the anticancer effect of sunitinib on renal cell carcinoma by inhibiting autophagy and inducing apoptosis - Li, Man-Li (Oncol Lett, 2018)
Sunitinib based adjuvant chemotherapy combined with chloroquine (CQ) for the treatment of renal cell carcinoma (RCC) is in clinical trials; however, its anti-RCC effect and the mechanism remain unclear. In the present study, the anti-RCC effect of sunitinib with CQ and the underlying mechanism was investigated. An MTT assay demonstrated that CQ enhanced the proliferation inhibitory effect of sunitinib against the OS-RC-2 RCC cell line. CQ inhibited sunitinib-induced autophagy in OS-RC-2, which was evidenced by the inhibition of autophagic vacuoles, acidic vesicular organelle formation, light chain 3 (LC3)-II recruitment to the autophagosomes and the conversion of LC3-I to LC3-II, as induced by sunitinib. The inhibition of autophagy by CQ enhanced sunitinib-induced apoptosis, which was characterized by the activation of caspase-3, caspase-9, Bcl-2 and p53. Additionally, the exposure of OS-RC-2 cells to CQ and sunitinib resulted in the inhibition of AKT, tuberous sclerosis complex 2, mechanistic target of rapamycin and p70 ribosomal S6 kinase, which are associated with cell proliferation. In in vivo study, a combination of sunitinib with CQ in mice significantly reduced OS-RC-2 cell xenograft growth compared with the sunitinib alone group. In conclusion, the present study demonstrated that CQ may enhance the anti-RCC effect of sunitinib by inhibiting the autophagy induced by sunitinib, and enhance the rate of apoptosis. Inhibiting cell proliferation may also serve a role in the synergistic antitumor effect of sunitinib and CQ. These data suggest that combination therapy of sunitinib with CQ may be a promising strategy for adjuvant chemotherapy in RCC.